HUMANISING ISLAMIC RELIGIOUS EDUCATION: A HOLISTIC CURRICULUM MODEL FOR CHARACTER DEVELOPMENT IN INDONESIA - Alhamuddin (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This study analysed the implementation of a humanisation-based Islamic Religious Education curriculum in Indonesian schools, focusing on its integration of character education. The conventional curriculum has predominantly emphasised cognitive and textual aspects, while the affective and psychomotor domains have remained underdeveloped. Using a qualitative approach, this research employed document analysis as its primary data collection method. Key documents—including syllabi, lesson plans, teaching guidelines, and national education policy frameworks related to the Merdeka Curriculum—were purposively selected and thematically analysed. The findings revealed that the humanisation-based curriculum incorporated core character values such as empathy, tolerance, responsibility, and honesty through dialogical, reflective, and experiential learning approaches. The model encouraged active student engagement, moral reflection, and the application of Islamic teachings to real-life social contexts. Educational stakeholders responded positively, highlighting the curriculum’s flexibility, contextual relevance, and alignment with national policy directions. In conclusion, the humanisation-based IRE curriculum provided a more holistic framework for character development by addressing not only cognitive, but also affective and behavioural dimensions. The study recommends further adoption and refinement of this model, alongside teacher training and policy support, to enhance its pedagogical impact.